Comparative genomics to bridge Vicia faba with model and closely-related legume species: stability of QTLs for flowering and yield-related traits - Cruz-Izquierdo, S; Avila, C.; Satovic, Z.; Palomino, C.; Gutierrez, N.; Ellwood, Simon; Phan, Huyen; Cubero, J.; Torres, A. (Springer, 2012)
This study presents the development of an enhanced map in faba bean. The map contains 258 loci, mostly gene-based markers, organized in 16 linkage groups that expand 1,875 cM, with an average inter-marker distance of 7.26 cM. The combination of EST-derived markers with a number of markers physically located or previously ascribed to chromosomes by trisomic segregation, allowed the allocation of eight linkage groups (229 markers), to specific chromosomes. Moreover, this approach provided anchor points to establish a global homology among the faba bean chromosomes and those of closely-related legumes species. The map was used to identify and validate, for the first time, QTLs controlling five flowering and reproductive traits: days to flowering, flowering length, pod length, number of seeds per pod and number of ovules per pod. Twelve QTLs stable in the 2 years of evaluation were identified in chromosomes II, V and VI. Comparative mapping suggested the conservation of one of the faba bean genomic regions controlling the character days to flowering in other five legume species (Medicago, Lotus, pea, lupine, chickpea). Additional syntenic co-localizations of QTLs controlling pod length and number of seeds per pod between faba bean and Lotus japonicus are likely. The new genetic map opens the way for further translational studies between faba bean and related legume species, and provides an efficient tool for breeding applications such as QTL analysis and marker-assisted selection.